Ontology-based Approach for Klungkung Royal Family - Ganeswara, Putu Ryan; Pramartha, Cokorda Rai Adi (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 8 No 4 (2020): JELIKU Volume 8 No 4, Mei 2020, 2020)
Kawitan genealogies form to strengthen family relations by staying in line with their ties. Today, there are many Balinese Hindu searches their heritance. This due to no explicit documentation about the family tree and the Balinese Hindu relies on people memories. To overcome this problem, we develop the ontology of the Family Tree Naritan Kawarya Narem Dalem Benculuk Tegeh Kori with Forward Chaining and Backward Chaining Search Method can overcome problems related to marriage lineage. By using the structured data in the form of an ontology, the computer agents and human will be able to find information related to their genealogy easily, so that there are no more people who are confused with their heritance. The ontology evaluation was conducted on the Nararya Dalem Benculuk Tegeh Kori's family tree. The initial result gave positive feedback toward further development of this ontology. Keywords : Ontology, Family Tree, Methontology